Evaluation Of Sensory And Bacteriological Quality Of Meatball Supplemented By Spirulina Platensis - Kareman S. Awadalla (Egyptian Society for Animal Management, 2020)
Spirulina "Superfood" is the common name of blue-green microalgae, which have a spiral cellular structure belonging to two genera Spirulina and Arthrospira which consist of (55-70% dry weight) protein, (5-6%) lipid, carbohydrates, vitamins, minerals and pigments. According to FDA Spirulina is approved and safe to be employed as a food additive. Ten kg of fresh minced meat was purchased from different retail markets within Ismailia province, mixed thoroughly with common salt and divided into seven portions; control, 0.5%, 1%, 1.5%, 2%, 3% and 5% concentrations of added Spirulina platensis powder. About 500g from control and treated samples were formed into small meatballs, refrigerated at 4oC and examined for sensory and bacteriological evaluation at (zero, 2, 3, 4, 6, 8 and 9 days) of storage. The results of this study showed that the addition of Spirulina platensis had an adverse effect on the colour of both raw and cooked meatball samples, but gave an acceptable smell. Consistency of raw meatball samples was acceptable at different concentrations of Spirulina platensis, while it was mildly affected in cooked meatball samples especially at 5% concentration. The Taste of cooked meatball samples was not affected by the addition of different concentrations of Spirulina platensis. The obtained results revealed that the addition Spirulina platensis has the ability to reduce the growth of total aerobic bacteria, Enterobacteriaceae spp. and Staphylococcus aureus.